Analisis Susut Energi Listrik pada Trafo Distribusi 160 KVA di Gardu Distribusi SP022 PLN ULP Sape Penyulang Sari Akibat Ketidakseimbangan Beban - Alfan Ediyasa Ulinnuha (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
This research aims to analyze the operational conditions of distribution transformers at the SP022 PLN ULP Sape substation, with a focus on calculating load imbalances caused by transformer losses. The data collected includes voltage and current measurements, as well as calculation analysis related to energy losses. The analysis results show that there is a significant load imbalance. Current measurement data shows that the load imbalance during the day is 9.967%, while at night it increases to 12.63%. The total transformer loss was recorded at 526,041 W during the day and 770,359 W at night. The energy losses that occur respectively are 15,556 kWh/day with an estimated loss cost of IDR 22,473.7 per day or 466,704 kWh per month with a loss cost of IDR 674,247.26 per month. The results of this research show that although losses due to imbalance are still within tolerance limits, regular repairs can reduce power losses and operational costs, thereby increasing the efficiency of distribution transformers.